The Reproducibility of the Immunohistochemical PD-L1 Testing in Non-Small-Cell Lung Cancer: A Multicentric Italian Experience. (14th April 2019) - Vigliar, Elena; Malapelle, Umberto; Bono, Francesca; Fusco, Nicola; Cortinovis, Diego; Valtorta, Emanuele; Spyridon, Alexiadis; Bimbatti, Manuela; Zocchi, Mario; Piva, Chiara; Gaudioso, Gabriella; Iaccarino, Antonino; et al.
Abstract : An important harmonization effort was produced by the scientific community to standardize both the preanalytical and interpretative phases of programmed death-ligand 1 (PD-L1) immunohistochemical (IHC) testing in non-small-cell lung cancer (NSCLC). This analysis is crucial for the selection of patients with advanced-stage tumors eligible for treatment with pembrolizumab and potentially with other anti-PD-1/PD-L1 checkpoint inhibitors. This multicentric retrospective study evaluated the reproducibility of PD-L1 testing in the Italian scenario both for closed and open platforms. In the evaluation of the well-known gold-standard combinations (Agilent 22C3 PharmDx on Dako Autostainer versus Roche's Ventana SP263 on BenchMark), the results confirmed the literature data and showed complete overlapping between the two methods. With regard to the performances by using open platforms, the combination of 22C3 with Dako Omnis or Benchmark obtained good results basically, while the 28, 8 clone seemed to be associated with worse scores.